KANDUNGAN LOGAM Pb DAN Cu DALAM BUAH STROBERI SERTA SPESIASI DAN BIOAVAILABILITASNYA DALAM TANAH TEMPAT TUMBUH STROBERI DI DAERAH BEDUGUL - Putu Desitha Pratiti Kameswari Wisnawa; I Made Siaka; Anak Agung Bawa Putra (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2016)
A study about speciation and bioavailability of heavy metals Pb and Cu in strawberry fruits and in the strawberry soils in Bedugul areas has been carried out. This study was aimed to determine the concentrations of Pb and Cu in the fruits and the soils, as well as speciation and bioavailabilities of both metals in the soils. Wet digestion method with reverse aqua regia was applied for determining the total metals, while sequential extraction method was performed to fractionate the metals bound to the various phases of the soils. The measurement of both metals was carried out by the use of AAS (Shimadzu, AA-7000). The total Pb and Cu contents in the fruits were 2.5903-9.2019 and 0.8744-1.1567 mg/kg, respectively while in the soils were 20,7912 -39.0144 and 39.3154-42,6620 mg/kg, respectively. In the speciation of both metals in soils, it was found that Pb and Cu associated with EFLE phases were 3.4944 and 1.2454 mg/kg, respectively, while those bound to Fe/Mn Oxides phases were 5.6652 and 3.1860 mg/kg, respectively. The Pb and Cu bound to organic/sulfide phases were 7.9553 and 5.5913 mg/kg, respectively and those bound to resistant phases were 13.4471 and 31.0796 mg/kg, respectively. Bioavailabilities of Pb and Cu in the soils were dominated by non bioavailable fractions, i.e. 43.69 and 76.11%, respectively, followed by the fractions of potentially bioavailable, and the lowest fractions were found as readily bioavailable.